Pengaruh Social Media Marketing dan Online Customer Review Menu terhadap Keputusan Pembelian Konsumen pada Lesehan Oha Doku di Kabupaten Dompu - Miratul Janah; Samsudin Samsudin; Risca Ariska Ramadhan (ProBisnis : Jurnal Manajemen, 2026)
This study aims to analyze the influence of social media marketing and online customer review menus on consumer purchase decisions at lesehan oha doku in dompu district. This study uses a quantitative approach. The population in this study is 8,800 accounts following the lesehan oha doku facebook page. The determination of the number of samples using the slovin formula with a margin of error of 10% was obtained by 98 respondents. The results of this study show that partially the social media marketing variable does not have a significant effect on purchase decisions, with a value of 0.535. And the online customer review variable has a significant effect on purchase decisions, with a Significance value (Sig.) of 0.001. Meanwhile, simultaneously it shows that the variables of social media marketing and online customer reviews menu together have a significant effect on purchase decisions, with a Significance value (Sig.) of 0.004.